Relationship of the optic nerve to the posterior paranasal sinuses among patients visiting a tertiary hospital of Gandaki Province of Nepal: A CT scan anatomic study - Pangeni, Roshan; Mallik, Mukesh; Bhattarai, Anupama; Pangeni Lamsal, Laxmi; Bagale, Deepak; Thapa, Madan; Bhandari, Rajan Mani; Ban, Tanka Raj (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Functional Endoscopic Sinus Surgery (FESS) has popularly been used for the effective treatment of paranasal sinus disorders and for the removal of tissue obstructing the osteo meatal complex and the facilitation of drainage. However, almost 16% to 50% of all the complications of the FESS have orbital involvement. The complications are due to the wide variation in the anatomy of the sphenoidal and posterior ethmoidal sinuses. This study aimed to find the prevalence of types of relationships that optic nerves have with the sphenoid sinus and also the prevalence of anatomical variation in sphenoid sinus. Methods: This is the descriptive cross-sectional study conducted over 210 participants appearing for CT scan imaging of paranasal sinuses. CT scan of paranasal sinus was performed with 5 mm thickness and then reconstructed to 1.5 mm thickness and evaluated to find the relationship of optic nerve with the paranasal sinuses according to Delano et al. classification. Prevalence of Onodi cells and anterior clinoid process pneumatization was also evaluated for variation in sphenoid sinus. Results: This study found that bilateral optic nerve of Type-I was found in 82.38% people followed by Type-IV in 14.29%. While, Type-III was completely absent in the study population. Prevalence of Onodi cells was 10.95% and that of ACP pneumatization was 6.67%. Conclusions: Variation in relationship of Optic Nerve with paranasal sinuses found with Type-I being the most common.